Analisis Pengendalian Internal Atas Sistem dan Prosedur Penerimaan dan Pengeluaran Kas Masjid Baiturrahim Samarinda - Muhammad Zaini; Siti Masyithoh; Salmah Pattisahusiwa (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2017)
Data’s research is result of observation by interview to chief and management of Baiturrahim Samarinda mosque. Theories which used to find out and analyze internal control of systems and procedures for cash receipts and disbursements are 1) organizational structure which separate responsibility, 2) Authorization and registration, 3) Well-practice, 4) Quality of  management in accordance with their responsibilities. Results of research show that systems and procedures for cash receipts of Baiturrahim Mosque is good to protect from fraud and manipulation of financial data because elements of cash receipt internal control which is used by Baiturrahim mosque is suitable with elements of cash receipt internal control. Systems and procedures for cash disbursements is weak because organizational structure that separates responsibility is not suitable with cash disbursement due to double job by one function and management doesn’t have balance sheet.